Policy Frameworks in the Post-Crisis Environment - Pain, Nigel (OECD Publishing, 2011)
The financial crisis revealed flaws in pre-crisis policy frameworks. Particular gaps included the failure of monetary and financial policies to incorporate fully the implications of the rapid pro-cyclical growth in financial leverage and risk-taking, especially across national borders, and the failure of fiscal policy to create sufficient space for policy manoeuvre in event of a crisis. During the crisis, the clear pre-crisis assignments of policy instruments to objectives became blurred, and the effectiveness of separate policy instruments became increasingly interdependent. In the early stages of the exit from the crisis, policy decisions continue to be made in an environment of high uncertainty. In the near term, important policy priorities are to support the recovery, to keep projected inflation close to target and to pursue internationally co-ordinated financial and structural reforms to enhance financial market resilience and strengthen the prospects for macroeconomic stability. In the medium term, the priority is to ensure that the overall policy framework is more robust than prior to the crisis, which may also require institutional reforms. There are good arguments for restoring a clear assignment of policy instruments to policy objectives and policy institutions, but for this to occur it will be especially important that well-founded and internationally consistent reforms to financial regulation and supervision are put in place
Keywords: Economics